The history of Bronze and Iron Age Israel - Matthews, Victor H. (Essentials of biblical studies, 2019)
"This volume provides a basic introduction to the historical, archaeological, and contextual aspects of ancient Israel during its formative period in the Bronze and Iron Age. It integrates extra-biblical sources with the biblical narrative in order to explore the development of ancient Israelite identity, cultural traditions, and their interaction with the other major cultures of the ancient Near East."--